Workload in Norwegian general practice 2018 - an observational study - Tone Morken; Ingrid Keilegavlen Rebnord; Kjell Maartmann-Moe; Steinar Hunskaar (BMC, 2019)
Abstract Background Rising workload in general practice has been a recent cause for concern in several countries; this is also the case in Norway. Long working hours and heavy workload seem to affect recruitment and retention of regular general practitioners (RGPs). We investigated Norwegian RGPs' workload in terms of time used on patient-related office work, administrative work, municipality tasks and other professional activities in relation to RGPs, and gender, age, employment status and size of municipality. Methods In early 2018, an electronic survey was sent to all 4716 RGPs in Norway. In addition to demographic background, the RGP reported minutes per day used on various tasks in the RGP practice prospectively during 1 week. Working time also included additional tasks in the municipality, other professional work and on out-of-hours primary health care. Differences were analysed by chi square test, independent t-tests, and one-way ANOVA. Results Among 1876 RGPs (39.8%), the mean total working hours per week was 55.6, while the mean for regular number of working hours was 49.0 h weekly. Men worked 1.5 h more than women (49.7 vs. 48.2 h, p = 0.010). Self-employed RGPs work more than salaried RGPs (49.3 vs. 42.5 h, p < 0.001), and RGPs age 55-64 years worked more than RGPs at age 30-39 (51.1 vs. 47.3 h, p < 0.001). 54.1% of the regular working hours was used on face-to-face patient work. Conclusions Norwegian RGPs have long working hours compared to recommended regular working hours in Norway, with small gender differences. Only half of the working time is used on face-to-face consultations. There seems to be a trend of increasing workload among Norwegian GPs, at the cost of direct patient contact. Further research should address identifying factors that can reduce long working hours.